2023
DOI: 10.1093/jncics/pkad001
|View full text |Cite
|
Sign up to set email alerts
|

Differential trends in rising endometrial cancer incidence by age, race, and ethnicity

Abstract: Endometrial cancer (EC) incidence is on the rise. Although early-onset endometrial cancer (EOEC, age at diagnosis <50) is relatively uncommon, the incidence of EOEC has been reportedly increasing in recent decades. However, the rising EOEC has not been thoroughly described with regard to the racial/ethnic disparities and in comparison with the late-onset EC (LOEC, age at diagnosis ≥50). We used the CiNA Analytic File, 1995-2018, from the North American Association of Central Cancer Registries (NAACCR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Several studies have found a similar increase in the incidence of early-onset uterine cancer, particularly among non-Hispanic Black and Hispanic women. [12][13][14][15] Guo et al 15 reported a notable annual percent increase in uterine cancer in younger age groups between 2001 and 2017: 3.6% among 20-29-year-olds and 3% among 30-39-year-olds. This increase in early-onset uterine cancer is also seen in other obesity-related cancers, including colorectal, multiple myeloma, gallbladder, kidney, and pancreatic cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found a similar increase in the incidence of early-onset uterine cancer, particularly among non-Hispanic Black and Hispanic women. [12][13][14][15] Guo et al 15 reported a notable annual percent increase in uterine cancer in younger age groups between 2001 and 2017: 3.6% among 20-29-year-olds and 3% among 30-39-year-olds. This increase in early-onset uterine cancer is also seen in other obesity-related cancers, including colorectal, multiple myeloma, gallbladder, kidney, and pancreatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, part of the cause of higher uterine cancer mortality rates among older non-Hispanic Black women and younger minority women could be attributed in part to the higher rates of obesity in these populations. [12][13][14][15]23 In 2017-2018, 39.8% of non-Hispanic White women, 43.7% of Hispanic women, 56.9% of non-Hispanic Black women, and 17.2% of non-Hispanic Asian or Pacific Islander women had obesity. 24 The higher levels of obesity seen among racial and ethnic minorities have been attributed to a wide variety of social and structural factors.…”
Section: Discussionmentioning
confidence: 99%
“…5) considers proximal (individual, biologic), intermediate (social and physical environments), and distal structural factors to best explain causes of disparities and their interplay. 78…”
Section: Ovarian Cancer Health Equity In the United Statesmentioning
confidence: 99%
“…Increased annual percentage change (2007-2019) is higher for non-Hispanic minority patients (Black, 2.4%; Asian/Pacific Islander, 2.5%; American Indian/Alaska Native, 2.5%) and Hispanic patients (2.9%) compared with NHWs (0.7%). 78 Those EC cases diagnosed at age younger than 50 years (early onset) have also increased among Black, Hispanic, and non-Hispanic Asian Pacific Islander patients compared with NHW women. 79 Early-onset EC tends to be hormonally driven and may be partially driven by trends in increasing obesity.…”
Section: Disparities In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation